ASPECTS OF SCIENCE AND TECHNOLOGY IN ANCIENT INDIA - Jha, Arun Kumar. ([S.l.])
1 online resource
Keywords: This book critically examines different aspects of scientific and technological development in Ancient India. It studies the special contribution of the history of science in our scientific understanding and its relationship with the philosophy and sociology of science. The volume: Discusses diverse and wide-ranging themes including Tibetan Buddhist tradition of neuro-biology; Sheds light on the unique developments within iron technology and urbanization in ancient Odisha; Studies the trajectory of proto-historic astronomy in India and the science of monsoon in early India; Evaluates the legacy of Aryabhata based on his major works related to astronomy and mathematics through a multidimensional perspective; Analyses the traditional knowledge of medicine in early India, the golden age of surgery with reference to the ancient Greek and Arabic systems of medicine, and the Buddhist influence on the science of medicine in Tibet. This book will be an essential read for scholars and researchers of ancient history, Indian history, history of science, history of technology, science and technology studies, and South Asian studies.